Religious issues as a message in political communications during local elections - Taufiq, Amal; Siahaan, Hotman M.; Pramono, Muhamad Fajar (Jurnal Studi Komunikasi, 2022)
This research focuses on religious issues used as messages in political communication. A campaign is a form of political communication by one of the candidates for local leader dan vice local leader of Gresik regency Sambari Qosim (SQ) in the 2015 regional election. This study employed a qualitative approach; therefore, the researcher used observation, in-depth interviews, and documentation to collect data. The study found that the SQ candidate pair used religious issues as a message in their political campaign because the local vice leader of Gersik Regency, Mohammad Qosim, was the son of a Kyai. Thus, such a strategy made it easier for him to gain sympathy from the voters, who would ultimately determine his choice of the pair. This strategy was implemented due to the socio-cultural community of Gresik Regency, a religious society that considers religion to be sacred, including the figure of a Kyai. As a religious figure, the Kyai must be obeyed and become an example in attitude and behaviour. This condition prompted the SQ candidate to take advantage of religious issues to gain as many votes as possible to win the 2015 regional elections.